Construções de verbos transitivos-predicativos em português: uma perspetiva transformacional - Baptista, Jorge (Revista da Associação Portuguesa de Linguística, 2021)
This article presents a proposal for the analysis of transitive-predicative verbal constructions, not derivable transformationally from completive constructions. The theoretical framework of operator-transformational grammar and the methodological principles of the reference framework of the Lexicon-Grammar are adopted herein. The article identifies a set of constructions and distinguishes them from other structures, usually identified as transitive-predicative structures in the literature